2014
DOI: 10.1177/1352458513519354
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic intervention for increasing self-directed exercise behaviour and improving important health outcomes in people with multiple sclerosis: a randomised controlled trial

Abstract: Background: Exercise programmes that can demonstrate evidence of long-lasting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
136
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(140 citation statements)
references
References 34 publications
(44 reference statements)
3
136
1
Order By: Relevance
“…Other studies have reported improvements in functional capacity 34 and self-directed exercise behaviour 35 after different supervised exercise interventions, but observed regression to baseline levels at follow-up. In our study, 15/17 completers in the training group reported a continuation of self-guided resistance training in a community-based setting.…”
Section: Follow-up and Reproducibilitymentioning
confidence: 96%
“…Other studies have reported improvements in functional capacity 34 and self-directed exercise behaviour 35 after different supervised exercise interventions, but observed regression to baseline levels at follow-up. In our study, 15/17 completers in the training group reported a continuation of self-guided resistance training in a community-based setting.…”
Section: Follow-up and Reproducibilitymentioning
confidence: 96%
“…Indeed, in a 12 week resistance training program, in 42 multiple sclerosis (MS) patients, improved voluntary isometric contraction and muscle power were noted in those undergoing the training program as compared to those who did not [104]. Further, improvements to physical and psychological functioning, fatigue and quality of life are noted [105,106], in addition to, improved ambulatory function and mood status [107], in MS patients taking part in exercise activity. A 2 year blind, parallel-group, randomized controlled trial is currently being assessed in 240 multiple sclerosis patients, to determine the effects of exercise to reduce disability and to promote health [108].…”
Section: F Autoimmunitymentioning
confidence: 99%
“…6,8 Of four studies that assessed effects on objectively measured PA, 6 only one found a between-group difference in favour of the intervention immediately post-intervention but not at 6 months post-intervention. 1 One study has examined the effect of a behaviour-change intervention on self-reported sitting time in people with MS with positive results. 10 However, as PA and sedentary behaviour are distinct concepts, and guidelines recommend both increasing PA and reducing sedentary behaviour for health benefits, 11 interventions targeting both PA and sedentary behaviour are required.…”
Section: Msmentioning
confidence: 99%
“…Physical activity (PA) and reduced sedentary behaviour are associated with milder disability, better mental health and less fatigue among people with multiple sclerosis (MS). [1][2][3] However, people with MS are insufficiently active and spend prolonged time in sedentary behaviour. 4,5 Behaviour-change interventions are a potential method for increasing PA and reducing sedentary behaviour in people with…”
Section: Introductionmentioning
confidence: 99%